7(6x+5)=6(10x-7)

Simple and best practice solution for 7(6x+5)=6(10x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6x+5)=6(10x-7) equation:



7(6x+5)=6(10x-7)
We move all terms to the left:
7(6x+5)-(6(10x-7))=0
We multiply parentheses
42x-(6(10x-7))+35=0
We calculate terms in parentheses: -(6(10x-7)), so:
6(10x-7)
We multiply parentheses
60x-42
Back to the equation:
-(60x-42)
We get rid of parentheses
42x-60x+42+35=0
We add all the numbers together, and all the variables
-18x+77=0
We move all terms containing x to the left, all other terms to the right
-18x=-77
x=-77/-18
x=4+5/18

See similar equations:

| 0.03(x-1)+0.2x=0.02(x+1) | | 1/7(105+r)=29 | | X+3=6x-1 | | 3x-7+x+3=180 | | 5+(x-3)=x-2 | | 1/4m÷5=m | | x/8-2=5/16 | | 2.3x-1.6=8.8-2,9x | | y/6+6=-15 | | y/6+6=1-15 | | y=4(-5,3)-23 | | y=4(-5,3)+23 | | 10(x-4)+2(x-5)-5(x+16)=19 | | 3^r=18 | | 9n-3=-6 | | 0.7x-14=-3.5 | | t+t+4t–7=17 | | 3x+2(4+6x)=13 | | x=-3=5 | | 7+2=4x-9 | | 3r^2=12 | | 2x+25+55=180 | | 2/x+1=4/x×2 | | 3(x-7)+2(x+11)=4(x-13)-10 | | 8x+4=2x+17 | | 6x+4=4x+19 | | 5x+24=8x+39 | | (5x+3)=(3x=+7) | | 2(x+22)=48 | | 8-(4y-4)=4-5y | | (x-30)=4/{X/2-30} | | 4(w+8)=4+3w |

Equations solver categories